PENERAPAN MODEL PROJECT BASED LEARNING (PJBL)MENGGUNAKAN MEDIA DAUR ULANG SAMPAH SEBAGAI UPAYAMENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWAKELAS X SMA NEGERI 5 PEMATANGSIANTAR - Lubis, Mawar Salehani; Purba, Ika Rosenta; Siboro, Thiur Dianti; Saragih, Marlindoaman (Jurnal Metabio, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model with recycled waste media on the creativity and learning outcomes of class X students at SMA Negeri 5 Pematangsiantar. The background of this study is the low creativity of students in utilizing inorganic waste and the dominance of lecture methods in learning. The method used is quantitative with a pre-test and post-test control group design. The sample consisted of two classes, namely the experimental class without special treatment and the control class using the PjBL model. The instruments used included pre-test and post-test tests and creativity questionnaires. The results showed that the control class experienced a more significant increase than the experimental class. The average pre-test score of the experimental class increased from 69.19 to 80.29, while the control class increased from 72.94 to 84.12. The t-test produced tcount 2.345 ≥ ttable 1.668 at α = 0.05, indicating a significant effect. The ANCOVA test showed a significance of 0.001 (pre-test) and 0.003 (learning model), F = 9.460, and R² = 0.140. These results indicate that the PjBL model has an effect on students' creativity and learning outcomes. Students become more active, creative, and enthusiastic. Therefore, the PjBL model is recommended as an effective alternative for biology learning in schools.